La solidarité écologique, lien de droit d’une interdépendance au vivant - Olivier Barrière (VertigO, 2022)
The French legislator introduced the concept of ecological solidarity into the law in 2006 as a bio-ecological relationship between areas, and then this concept was established as a general principle in 2016 in the Environmental code by calling for the consideration of "the interactions of ecosystems, living beings and natural or developed environments" in decision-making. Even with a restrictive definition of ecological solidarity, avoiding mentioning any interdependence, its introduction into the law is a major step towards an overcoming that will allow an indispensable transformation of modern Western society in the face of the ecological emergency (climate, health, biodiversity). The analysis of the input of this solidarity of living beings must be perceived as a Trojan horse in the cave of naturalism. State law will have to reinvent itself by getting out of a development scheme. It must operate a mutation articulated around a common relational ontology, called "coviabilist", within the framework of a legal pluralism. This reinvention of law can only be achieved by bringing together the societies of the Living, human and non-human making socio-ecosystem. Ecological solidarity opens the perspectives of a right/law of coviability by formalizing the interactions within living beings and environments through the link of viability, as a link of right.